Pengaruh Ukuran Perusahaan, Financial Distress dan Profitabilitas terhadap Ketepatan Waktu Penyampaian Laporan Keuangan pada Perusahaan Subsektor Pertambangan yang Terdaftar di BEI - Cindy Claudia; Joni Hendra; Mutimmah Rustianawati (CV. Ulil Albab Corp, 2024)
This study focused on companies in the mining subsector listed on the IDX from 2020 to 2022, aiming to investigate the positive impacts of Company Size, Financial Distress, and Profitability on the timeliness of financial statement submissions among these companies. The type of research used is quantitative, with an associative approach, involving variables such as Company Size, Financial Distress, and Profitability. To determine the extent of their positive influence on the timeliness of financial statement submission, this is demonstrated by the outer loading values with a significance level > 0.5. The study sample comprised 26 companies observed over a three-year period. Data for the research were sourced from www.idx.co.id and https://lembarsaham.com. The findings reveal that the Company Size variable positively influences the timeliness of financial statement submissions, Financial Distress also has a positive impact on submission timeliness, whereas Profitability does not significantly affect the timeliness of financial statement submissions among mining subsector companies listed on the IDX for the period 2020 to 2022.